ANALISIS KELAYAKAN EKONOMI DAN OPTIMASI FORMULASI PEMPEK LENJER SKALA INDUSTRI - Karneta, Railia (Publikasi Penelitian Terapan dan Kebijakan, 2010)
Pempek is a kind of traditional food for South Sumatera people, which is potentially to be developed into large scale of industry if its technology meets standart procedure and consistent quality. Now a days, current pempek activity has adjusted its formula and technology to changes of the existing materials as well as their prices. The study investigated people’s perception on pempek taste, optimalized pempek’s formula, minimized material cost and analized it’s feasible enterpreneurship. Optimalization formula and minimization testing-using LINDO-Linier Programing Computer’s Program- shows that condition using 100 grams of pempek. Minimum cost of pempek’s material is Rp 2310,04,- per 100 grams pempek’s formula. The feasibility study shows that 1000 lenjer per day production is feasible for industry scale. NPV test shows positive, IRR higher than current interest and Net B/C ration more than 1, PBP 1,69 per year and BEP 32,60 %. Sensitivity test to the increasing of costs and decreasing of return to 15 percent, pempek activity is still feasible to be done.